1993
DOI: 10.7164/antibiotics.46.374
|View full text |Cite
|
Sign up to set email alerts
|

5-N-Acetylardeemin, a novel heterocyclic compound which reverses multiple drug resistance in tumor cells. I. Taxonomy and fermentation of the producing organism and biological activity.

Abstract: The ardeemins are a new family of secondary metabolites produced by submerged fermentation of a fungus which was isolated from a soil sample collected in Brazil. Based on taxonomic studies, the producing culture was identified as Aspergillus fischeri var. brasiliensis strain AB 1826M-35. 5-7V-Acetylardeemin potentiated the cytotoxicity of the anticancer agent vinblastine in multidrug resistant humantumorcells.Multidrug resistance (MDR)is characterized by the development of resistance to several structurally un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…C-ring rigidification by unsaturation did not lead to increased activity (compound 5h), even though it was accompanied by an increase in lipophilicity due to the introduction of a bromine substituent, which is very often accompanied by an increase MDR in reversal actvity [1]. A similar increase in lipophilicity associated with the introduction of a prenyl substituent in compound 5i actually decreased its activity compared with that of 5 e , which has a similar stereochemistry, although this was probably associated with the lack of the N-acetyl group, which seems to be important for the activity of N-acetylardeemin [3]. Similarly, the lipophilic seco analogue 6, lacking a N-acetyl group, was inactive.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…C-ring rigidification by unsaturation did not lead to increased activity (compound 5h), even though it was accompanied by an increase in lipophilicity due to the introduction of a bromine substituent, which is very often accompanied by an increase MDR in reversal actvity [1]. A similar increase in lipophilicity associated with the introduction of a prenyl substituent in compound 5i actually decreased its activity compared with that of 5 e , which has a similar stereochemistry, although this was probably associated with the lack of the N-acetyl group, which seems to be important for the activity of N-acetylardeemin [3]. Similarly, the lipophilic seco analogue 6, lacking a N-acetyl group, was inactive.…”
Section: Discussionmentioning
confidence: 89%
“…brasiliensis, which has a very potent MDR reverser activity (IC 50 = 5-30 µM) and low toxicity. This compound is able to potentiate the cytotoxicity of vinblastine, doxorubicin or paclitaxel in multidrug resistant human tumour cells with 10-fold potency with respect to verapamil, the standard anti-MDR drug [3]. Its glycine analogue (1b) and its trifluoro derivative are also potent Fig.…”
Section: Mdr Reversal By Deprenylated Tetracyclic and Hexacyclic Analmentioning
confidence: 97%
See 1 more Smart Citation
“…Quinazolinone and quinazolinedione derivatives are of considerable interest because of their wide array of pharmacological properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. We have been specifically interested in the synthesis of novel heterocycles containing the quinazoline-2,4-dione backbone, which are known to exhibit potential anti-hypertensive properties [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, McAlpine and coworkers (7)(8)(9) have reported that the pyrroloindoline 5-N-acetylardeemin demonstrates the ability to restore vinblastine sensitivity to tumor cell lines that manifest ''operational resistance'' to cytotoxic agents. The hydroxypyrroloindoline gypsetin has evoked interest as a potential inhibitor of the enzyme acyl-CoA:cholesterol acyltransferase and as such might find therapeutic use as a cholesterol-lowering agent (10)(11)(12).…”
mentioning
confidence: 99%